HUBUNGAN PENDEKATAN HEUTAGOGI, FASILITAS PEMBELAJARAN DAN TEACHER DIGITAL COMPETENCE (TDC) DENGAN KREATIVITAS GURU DI SMP NEGERI KABUPATEN BLITAR - Amanda Putri, Nia; Budi Wiyono, Bambang; Sultoni (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2023)
Information and communication in Indonesia are developing rapidly, as is education. One of the pillars of education is educators or teachers. improving the quality of teachers prepared for the younger generation in accordance with the work and social world of the 21st century. Learning based on Information and Communication Technology (ICT) is a competency that teachers must master in the 21st century. The research was conducted at Blitar District Public Middle School. Research was conducted to determine the relationship between the heutagogical approach (X1), learning facilities (X2), teacher digital competence (TDC) (X3) and teacher creativity (Y) at Blitar Regency Public Middle Schools.The research uses a quantitative approach with a descriptive correlational research design. The population in the study used 10 State Middle Schools in Blitar Regency. The sampling technique used in the research is cluster sampling. So, the sample used was 226 teachers. data collection using questionnaires and analysis techniques using paths with SmartPLS.The results of the research show that in the bootstrapping hypothesis test (1) there is a relationship between the heutagogical approach and teacher creativity with a P value of 0.040 <0.05. (2) there is a relationship between learning facilities and teacher creativity with a P value of 0.000 <0.05. (3) there is a relationship between teacher digital competence and teacher creativity with a P value of 0.013<0.05. (4) there is a relationship between the heutagogical approach and teacher digital competence with a P value of 0.000 <0.05. (5) there is a relationship between learning facilities and teacher digital competence with a P value of 0.024 <0.05. (6) there is an indirect relationship between teacher digital competence which plays a role in the relationship between the heutagogical approach and teacher creativity, P Value 0.023<0.05 (7) there is no indirect relationship between teacher digital competence which plays a role in learning facilities and teacher creativity, P Value 0.169>0.05. Key Words: Learning Facilities, Teacher Creativity, Teacher Digital Competence Heutagogical Approach.